Single frequency whole-body impedance studies in children with diarrhoeal disease and development of a variable frequency system - Moshal, David Clive; Moshal, David Clive (Division of Biomedical Engineering, 2017)
Diarrhoeal disease is a major cause of infant mortality in this and other developing countries. The assessment of the degree of dehydration in these children is often based on subjective findings alone. These have been shown to be inaccurate as an assessment of the degree of dehydration. Whole-body impedance (WBI) is a method of measuring total body water which is used to assess body composition. This WBI technology, which operates at a single frequency, has been applied to the assessment of dehydration in children with diarrhoeal disease. The normal range of WBI was determined on a group of normally hydrated children and was found to have a mean of 746 Ω, a standard deviation of 85 Ω and 95 % confidence interval for the mean from 720 Ω to 772 Ω. WBI did not depend on age, mass, height or sex. The WBI of a group of children dehydrated from infantile gastroenteritis was measured both before and after rehydration. The dehydrated group had a mean WBI on admission of 1089 Ω and a standard deviation of 149 Ω with a 95 % confidence interval for the mean from 950 Ω to 1109 Ω. This value was significantly greater than that of the normal group. The WBI of the dehydrated group after rehydration was not significantly different from the normal group. In addition a variable frequency bioimpedance analyser was designed and tested. It was found to have an error of less than 1 % over the frequency range 1 to 100 kHz. The device was evaluated on 11 normal and dehydrated children. Four dehydrated children were tested before and after rehydration and this data was compared to a standard electrical model for WBI. It was found that the model could represent the measured data over this frequency range. The extracellular resistive element of the model was mainly responsible for the changes seen during rehydration, suggesting that dehydration in gastroenteritis is mainly due to fluid loss from the ECF compartment.